2014
DOI: 10.1002/hipo.22358
|View full text |Cite
|
Sign up to set email alerts
|

Acute melatonin treatment alters dendritic morphology and circadian clock gene expression in the hippocampus of Siberian Hamsters

Abstract: In the hippocampus of Siberian hamsters, dendritic length and dendritic complexity increase in the CA1 region whereas dendritic spine density decreases in the dentate gyrus region at night. However, the underlying mechanism of the diurnal rhythmicity in hippocampal neuronal remodeling is unknown. In mammals, most daily rhythms in physiology and behaviors are regulated by a network of circadian clocks. The central clock, located in the hypothalamus, controls melatonin secretion at night and melatonin modifies p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 52 publications
(87 reference statements)
1
23
0
1
Order By: Relevance
“…Furthermore, Bracci et al [216] reported that alterations in peripheral clock gene expression, i.e., a significantly higher expression of BMAL1, CLOCK, NPAS2, PER1, PER2, and REVERBα and a lower expression of PER3, CRY1 and CRY2, were found at the beginning of the morning shift after a day off in rotating shift work nurses as well as significantly higher 17-β-estradiol levels compared to daytime nurses. Another study reported that both Period1 and BMAL1 expression increased in the hippocampus of Siberian hamsters after acute melatonin treatment of 20 μg/day, accompanied by the alterations of dendritic morphology, indicating melatonin could act as a signal to coordinate the circadian rhythm in neuronal remodeling [217]. Additionally, melatonin was found to adjust the expression pattern of clock genes (per1, per2, bmal1 and clock) in the SCN mainly by increasing amplitude in their expressional rhythms without inducing robust phase shifts in them.…”
Section: Bioactivities Of Melatoninmentioning
confidence: 99%
“…Furthermore, Bracci et al [216] reported that alterations in peripheral clock gene expression, i.e., a significantly higher expression of BMAL1, CLOCK, NPAS2, PER1, PER2, and REVERBα and a lower expression of PER3, CRY1 and CRY2, were found at the beginning of the morning shift after a day off in rotating shift work nurses as well as significantly higher 17-β-estradiol levels compared to daytime nurses. Another study reported that both Period1 and BMAL1 expression increased in the hippocampus of Siberian hamsters after acute melatonin treatment of 20 μg/day, accompanied by the alterations of dendritic morphology, indicating melatonin could act as a signal to coordinate the circadian rhythm in neuronal remodeling [217]. Additionally, melatonin was found to adjust the expression pattern of clock genes (per1, per2, bmal1 and clock) in the SCN mainly by increasing amplitude in their expressional rhythms without inducing robust phase shifts in them.…”
Section: Bioactivities Of Melatoninmentioning
confidence: 99%
“…Similarly, Yuan et al [21] observed significant changes in cell morphology when cells were treated with TUB-A and PdNPs. Furthermore, MLT has also been shown to alter cell morphology; Reddins et al [55] reported that MLT altered the ultrastructure of mouse Leydig cells, possibly affecting their capacity to secrete steroids, while Ikeno et al [56] reported that MLT induced structural changes of hippocampal neurons, increasing apical dendritic length and complexity and reducing the dendritic spine density. The combination of MLT with all-trans retinoic acid and somatostatin also caused a series of morphological alterations, including pyknotic nuclei, swollen mitochondria with disrupted cristae, autophagic vesicles, and dissolution of the plasma membrane associated with spillage of the cytoplasmic content.…”
Section: Combining Pdnps With Mlt Altered Cell Morphologymentioning
confidence: 99%
“…In aged rats, long‐term melatonin treatment attenuates the decrease in dendritic protein MAP‐2 immunostaining and improves dendritic stability, thus diminishing synaptic elimination (Prieto‐Gomez et al, ). Acute melatonin treatment increases apical dendritic length and dendritic complexity in the CA1 region (Ikeno & Nelson, ). In our previous study, we also found that melatonin treatment rescues the dendritic spine impairments induced by scopolamine (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%